The Impact of Malaysian Private Entity Reporting Standard (MPERS) Adoption on the Value Relevance and Timeliness of Financial Reporting by Small and Medium Enterprises (Smes): A Conceptual Framework - Siti Nur Ayuni Rosli; Nurul Nazlia Jamil (Human Resource Management Academic Research Society, 2024)
Indexed by ERA